Archaeology of salt : approaching an invisible past - Brigand, Robin; Weller, Olivier (Sidestone Press, 2015)
Salt is an invisible object for research in archaeology. However, ancient writings, ethnographic studies and the evidence of archaeological exploitation highlight it as an essential reference for humanity. Both an edible product and a crucial element for food preservation, it has been used by the first human settlements as soon as food storage appeared (Neolithic). As far as the history of food habits (both nutrition and preservation) is concerned, the identification and the use of that resource certainly proves a revolution as meaningful as the domestication of plants and wild animals. On a gl.